Insularidad y meteorología: espacios re-expresados y sub-versivos en la narrativa contemporánea cubana - Pérez Medrano, Cuauhtémoc (2016)
On the island of Cuba, meteorological phenomena have been important metaphorical elements in the configuration of the country’s creation stories. For this reason, it could be useful to observe historical, sociocultural phenomena as meteorological in nature as that would explain many local and global questions regarding cultural identity and diversity, and aesthetic and literary studies. Insularity in Cuba has been analyzed from several different perspectives ranging from ontological to political or literary in nature. The interaction between real and imaginary space in literature demands an approach somewhere between “real” and meta-literary. Throughout the cultural history of Cuba, use of the island metaphor has been a constant and for the past 30 years or so, generations ofuban writers have sought to overcome idiothematic and stylistic obstacles through the re-expression of their own literary subversions. For these authors, insularity or the island itself becomes aversatile topic that places stress on the relationship between aesthetical aspects and their categories.These literary phenomena would be noticeable in the stories of Abilio Estevez, Marilyn Bobes and Antonio Jose Ponte, which would give rise to an interdisciplinary debate surrounding the global positioning of Cuban fiction and contemporary literary subversions.